Pengaruh Lembar Kerja Peserta Didik Berbasis Guided Writing terhadap Keterampilan Menulis Tegak Bersambung Kelas II SDN 170 Mulyasri Kabupaten Luwu Timur - Milia Sugiarti; Syahruddin Syahruddin; Ratnawati Ratnawati (Departement of Mathematics Education, 2024)
The main problem in this research is the lack of innovative teaching materials for students to practice cursive writing. This research aims to describe the effect of guided writing-based student worksheets (LKPD) on the cursive writing skills of class II students at SDN 170 Mulyasri, East Luwu Regency. This type of research is quantitative research that uses experimental research (pre-experimental design) with a one-group pretest-posttest design. The population in this study were all class II students at SDN 170 Mulyasri, East Luwu Regency with a sample size of 22 students. The research instruments used to collect data were description tests (pretest-posttest) and observation. The data analysis technique used in this research uses descriptive statistical analysis and inferential statistical analysis with the t test. The results of the research prove that there is an influence of guided writing-based LKPD on the cursive writing skills of class II students at SDN 170 Mulyasri, East Luwu Regency.